2019
DOI: 10.3389/fneur.2019.00836
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Assessment of Hand Spasticity After Stroke: Imaging Correlates and Impact on Motor Recovery

Abstract: Objective: This longitudinal observational study investigated how neural stretch-resistance in wrist and finger flexors develops after stroke and relates to motor recovery, secondary complications, and lesion location. Methods: Sixty-one patients were assessed at 3 weeks (T1), three (T2), and 6 months (T3) after stroke using the NeuroFlexor method and clinical tests. Magnetic Resonance Imaging was used to calculate weighted corticospinal tract lesion load (wCST-LL) and to per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 60 publications
5
37
0
Order By: Relevance
“…The aim of this study was to explore if assessed and perceived functioning and disability was affected by using the Mollii® suit for treatment of spasticity in the home setting for 6 weeks. In line with previously reported results from the same study setting [38], approximately 2/3 of the screened eligible participants were found to have a clinically detectable neural component exceeding the cut off for spasticity according to the NeuroFlexor™. Thus, the participants included in this study may be considered representable for a slightly younger stroke population (mean age 58 years), living with hemiplegia and spasticity longterm after stroke.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The aim of this study was to explore if assessed and perceived functioning and disability was affected by using the Mollii® suit for treatment of spasticity in the home setting for 6 weeks. In line with previously reported results from the same study setting [38], approximately 2/3 of the screened eligible participants were found to have a clinically detectable neural component exceeding the cut off for spasticity according to the NeuroFlexor™. Thus, the participants included in this study may be considered representable for a slightly younger stroke population (mean age 58 years), living with hemiplegia and spasticity longterm after stroke.…”
Section: Discussionsupporting
confidence: 90%
“…In this study we used the standardized evaluated NeuroFlexor™ method to quantify and differentiate the neural, i.e. spasticity, elastic and viscosity components of an increased resistance to passive stretch [ 21 , 25 27 , 38 ]. The observation of stable baseline the NC values before the start of the intervention (A1-A3) lends strong support to the observed significant changes in the NC between the start (M1) and the end of the intervention (M2).…”
Section: Discussionmentioning
confidence: 99%
“…The robotic-therapy was effective at releasing spasticity at the wrist-joint with ~ 26% (p = 0.03) improvement over ~ 14% in CG. The regaining normal muscle-tone is considered as a predictor of recovery or the rst-step in recovery (22) followed by an increase in muscle-strength and improvement in functional movements or ADL, nally leading to muscle-strength. In this study, AROM and Barthel-Index have been measured as the indicators of ADL (Table-2).…”
Section: Comparison Of Clinical-scales Of Robotic-therapy Group With mentioning
confidence: 99%
“…In other words, this spasticity increases stiffness of the finger joints and furthermore leads to a decrease of their range-of-motion (ROM), creating severe reduction to hand function (Sadarangani et al, 2017). As spasticity and motor recovery are both related to neural plasticity after stroke, to lead targeted rehabilitation interventions, it is suggested that clinicians should decide the best treatment option for each patient based on their spasticity condition (Hong et al, 2018;Jeanette et al, 2019). In current clinical practice, primary measures (Bohannon and Smith, 1987;Copley and Kuipers, 1999;Gregson et al, 1999;Mackey et al, 2004) such as Modified Ashworth Scale (MAS), Modified Tardieu Scale (MTS), Tone Assessment Scale, and King's Hypertonicity Scale are widely used to grade the resistance on the joints during passive soft tissue stretching (Thibaut et al, 2013).…”
Section: Introductionmentioning
confidence: 99%